L2 Processing of Plural Inflection in English. Issue 2 (June 2015) - Song, Yoonsang
<x xml:space="preserve">Abstract</x> This study investigates (1) whether late second language (L2) learners can attain native‐like knowledge of English plural inflection even when their first language (L1) lacks an equivalent and (2) whether they construct hierarchically structured representations during online sentence processing like native speakers. In a self‐paced reading task, native English speakers and advanced Korean learners of English were tested on their (in)sensitivity to plural errors in two different structures. The results indicate that despite the L1–L2 difference, the learners were sensitive to plural errors in both structures, and that their sensitivity to the errors was affected by the structural distance of the feature‐checking dependency related to plural inflection, like the native speakers' sensitivity. These findings suggest that (1) L2 learners can acquire target‐like L2 inflection knowledge, even if such inflection is not present in their L1, contra the representational deficit account and that (2) they are sensitive to structural distance because they compute hierarchically structured representations during real‐time language comprehension, contra the shallow structure hypothesis.